A comprehensive overview of the cystic fibrosis on the island of São Miguel (Azores, Portugal) - Joana Rosa; Patrícia Gaspar-Silva; Paula Pacheco; Conceição Silva; Cláudia C. Branco; Barbara S. Vieira; Alexandra Carreiro; Juan Gonçalves; Luisa Mota-Vieira (BMC, 2020)
Abstract Background Early diagnosis and treatment are improving significantly the quality of life of patients with cystic fibrosis (CF). This recessive disease is caused by a great variability of mutations in the CF transmembrane conductance (CFTR) gene, whose spectrum and frequency can be different across populations. Methods We performed a retrospective cross-sectional study of CF patients from the island of São Miguel (Azores, Portugal) through a clinical, genealogical, genetic and epidemiological investigation. The clinical course of patients was analyzed as a whole and according to their genotype. Results We identified 14 CF patients within a 23-year period, corresponding to a cumulative incidence of 1:3012 births, being three of them born from consanguineous unions. Genetic analysis revealed three CFTR genotypes: p.[Ser4Ter];[Gln1100Pro] was present in one patient with a less severe phenotype (1/14); c.[120del23];p.[Phe508del], a very rare one (2/14); and p.[Phe508del];[Phe508del] in the remaining patients (11/14). Clinically, respiratory infections (8/14) and growth failure (6/14) were the most common initial manifestations. All patients presented pancreatic dysfunction, with 21.4 and 100% of them showing endocrine and exocrine insufficiency, respectively. As expected, patients with severe phenotype were homozygous for p.Phe508del and had the lowest value of body mass index. Conclusions The present study demonstrated that São Miguel Island has an increased incidence of CF when compared to recent Portuguese data (1:7500 live births). It also allowed a comprehensive overview of CF in São Miguel, improving medical practice along with genetic counselling and creating opportunities for genotype-targeted therapies.